Introducing enhanced recovery after surgery in a high-volume orthopaedic hospital: a health technology assessment - Francesco Vanni; Emanuela Foglia; Federico Pennestrì; Lucrezia Ferrario; Giuseppe Banfi (BMC, 2020)
Abstract Background The number of patients undergoing joint arthroplasty is increasing worldwide. An Enhanced Recovery After Surgery (ERAS) pathway for hip and knee arthroplasty was introduced in an Italian high-volume research hospital in March 2018. Methods The aim of this mixed methods observational study is to perform a health technology assessment (HTA) of the ERAS pathway, considering 938 procedures performed after its implementation, by means of a hospital-based approach derived from the EUnetHTA (European Network for Health Technology Assessment) Core Model. The assessment process is based on dimensions of general relevance, safety, efficacy, effectiveness, economic and financial impact, equity, legal aspects, social and ethical impact, and organizational impact. A narrative review of the literature helped to identify general relevance, safety and efficacy factors, and a set of relevant sub-dimensions submitted to the evaluation of the professionals who use the technology through a 7-item Likert Scale. The economic and financial impact of the ERAS pathway on the hospital budget was supported by quantitative data collected from internal or national registries, employing economic modelling strategies to identify the amount of resources required to implement it. Results The relevance of technology under assessment is recognized worldwide. A number of studies show accelerated pathways to dominate conventional approaches on pain reduction, functional recovery, prevention of complications, improvements in tolerability and quality of life, including fragile or vulnerable patients. Qualitative surveys on clinical and functional outcomes confirm most of these benefits. The ERAS pathway is associated with a reduced length of stay in comparison with the Italian hospitalization average for the same procedures, despite the poor spread of the pathway within the country may generate postcode inequalities. The economic analyses show how the resources invested in training activities are largely depreciated by benefits once the technology is permanently introduced, which may generate hospital cost savings of up to 2054,123.44 € per year. Conclusions Galeazzi Hospital's ERAS pathway for hip and knee arthroplasty results preferable to traditional approaches following most of the HTA dimensions, and offers room for further improvement. The more comparable practices are shared, the before this potential improvement can be identified and addressed.